Circular - Scotsman; Brockway, Fenner, 1888-1988
1938-08-24 INDEPENDENT LABOUR PARTY NATIONAL ADMINISTRATIVE COUNCIL Chairman : J. MAXTON. MP. Hon. Treasurer : F. W. JOWETT Telephone : Central 3196 Telegrams : Ilper, Lud, London Secretary : A. FENNER BROCKWAY, 35 St. Bride Street, London, E.C.4. Copy of paragraph in "The Scotsman" of August 24, 1938 P.O.U.M. LEADERS FOR TRIAL AT BARCELONA (From our own correspondent) Barcelona, August 23. The Tribunal of Espionage and High Treason announced to-day that the long delayed trials of the leaders of the Extreme Left P.O.U.M., many of them imprisoned during the Barcelona uprising of a year ago last May, will be begun on August 30. The P.O.U.M. organisation, a part of which admittedly followed the Trotskyist leadership, and which was known for its attacks on the Government, has long since beon silenced. The Barcelona uprising of May 1937 which it sponsored was responsible for the overthrow of the Largo Caballero Government and the succession to power of Premier Negrin. 292/946/24/14